Fabrication and characteristics of out-of-plane piezoelectric micro grippers using MEMS processes - Jeon, Chang-Seong; Park, Joon-Shik; Lee, Sang-Yeol; Moon, Chan-Woo (ELSEVIER SCIENCE SA, 2007)
Out-of-plane type piezoelectric micro grippers (briefly, OPPMG) actuated by micro cantilevers using sol-gel multi-coated PZT (Ph (Zr0.52Ti0.48)03) films with the thickness of 1.2 mu m were newly designed and fabricated using MEMS processes. Electromechanical and gripping characteristics of fabricated micro PZT cantilevers and OPPMG using them have been investigated. Two types of micro PZT cantilevers were fabricated with two types of supporting layers, respectively. The OPPMG was formed by two micro PZT cantilevers of the same type facing each other across the spacer of polyimide (PI). Precise gripping and positioning of metallic ball with diameter of 100 mu m using fabricated OPPMGs was successfully done at a low actuating voltage of 7 V, without any adhesion problems between two jaws of gripper and the ball. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ACTUATOR